Sosialisasi Program Surveilans Malaria (PSM) di Kabupaten Purworejo sebagai Upaya Pengendalian dan Pencegahan Penularan Malaria - Hubi Rahmat Andika; Helti Pebriyanti; Desiana Firdaus (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Malaria remains a public health concern in several regions of Indonesia, including Purworejo Regency, which reported an Annual Parasite Incidence (API) of 0.063 per 1,000 population in 2023. A total of 49 cases were reported, consisting of 36 indigenous and 13 imported cases (Balai Kesehatan Masyarakat Magelang, 2024). Community education and capacity building of health cadres are key strategies in malaria control and elimination. This community service activity aimed to provide education and training on malaria surveillance programs to health workers and the community, while also involving students in strengthening community-based prevention programs. The activities were carried out in two stages: (1) training and identification of malaria vectors on April 22, 2024, in Loano Subdistrict, and (2) mosquito larvae survey on May 14, 2024, in Banyuurip Asri Housing Complex. The program was successfully implemented, showing an increase in participants' knowledge and the discovery of mosquito larvae in several locations. This activity supportthe continuation of the Mosquito Nest Eradication (PSN) program by the Purworejo District Health Office.